Our Data, Ourselves : A Personal Guide to Digital Privacy - Lipton, Jacqueline D. (University of California Press, 2022)
A practical, user-friendly handbook for understanding and protecting our personal data and digital privacy. Our Data, Ourselves addresses a common and crucial question: What can we as private individuals do to protect our personal information in a digital world? In this practical handbook, legal expert Jacqueline D. Lipton guides readers through important issues involving technology, data collection, and digital privacy as they apply to our daily lives.Our Data, Ourselves covers a broad range of everyday privacy concerns with easily digestible, accessible overviews and real-world examples. Lipton explores the ways we can protect our personal data and monitor its use by corporations, the government, and others. She also explains our rights regarding sensitive personal data like health insurance records and credit scores, as well as what information retailers can legally gather, and how. Who actually owns our personal information? Can an employer legally access personal emails? What privacy rights do we have on social media? Answering these questions and more, Our Data, Ourselves provides a strategic approach to assuming control over, and ultimately protecting, our personal information.